Analysis of Environmental Knowledge Program Characteristics and Key Competencies to Support Sustainability - Tiro, Abdul Rachman; Surtikanti*, Hertien Koosbandiah; Riandi, Riandi; Nahadi, Nahadi; Irianti, Mustika; Gudivada, Sudarsanam; Anakotta, Raisa; Walukow, Auldry F. (Jurnal IPA & Pembelajaran IPA, 2025)
Higher education plays a strategic role in shaping character and providing learning experiences to acquire knowledge through effective learning by developing cognitive, affective, and psychomotor domains. The implementation of the merdeka belajar-kampus merdeka (MBKM) curriculum requires integration with local wisdom values to achieve the sustainable development goals (SDGs) through the development of 8 key competencies for sustainability. This research aims to analyze the implementation of environmental science lectures and measure the level of achievement of the 8 key competencies for sustainability among science education students in West Papua. Using a mixed methods approach, the research involves 30 seventh-semester students and one lecturer who teaches the course. Data collection methods include document studies, field observations, competency measurement using standardized instruments, and semi-structured interviews. Researchers analyze the data descriptively, both qualitatively and quantitatively. Analysis shows variations in the achievement of sustainability competencies, with the highest value in systems thinking competency (70.95) and the lowest in anticipatory competency (53.45). A gap exists in the implementation of learning, which does not optimally integrate local wisdom and the development of sustainability competencies. Therefore, developing an integrated curriculum considering the local context of West Papua, improving teacher capacity, and strengthening strategic partnerships are necessary to enhance the effectiveness of learning in developing the sustainability competencies of Science Education students